2012
DOI: 10.18632/oncotarget.542
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalization of death receptors correlates with cellular resistance to their cognate ligands in human breast cancer cells

Abstract: ABSTRACT:Multiple clinical trials are ongoing to evaluate the potential antitumor activity of human TNF variants, Fas ligand (FasL), TNF-related apoptosis inducing ligand (TRAIL) and its agonistic antibodies. These drug products act through the death receptors (DRs) TNF receptor 1 (TNFR1), Fas/CD95, DR4 (TRAIL-R1) and/or DR5 (TRAIL-R2), respectively. Therefore, characterization of the level and localization of DR expression in cancer cells is important for DR-targeted therapy. In this study, we examined the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…Similar results were obtained by stratifying patients according to TRAIL-receptors intensity staining scores. However, membrane staining for TRAIL-R2 was associated with a better prognosis in a subgroup of patients without nodal metastases at the time of surgery, which is consistent with recent evidence that the fraction of membrane-bound receptors determines their functional status [11], [31] and plays a major prognostic role in patients with hepatocellular carcinoma [8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were obtained by stratifying patients according to TRAIL-receptors intensity staining scores. However, membrane staining for TRAIL-R2 was associated with a better prognosis in a subgroup of patients without nodal metastases at the time of surgery, which is consistent with recent evidence that the fraction of membrane-bound receptors determines their functional status [11], [31] and plays a major prognostic role in patients with hepatocellular carcinoma [8].…”
Section: Discussionsupporting
confidence: 87%
“…the fraction of tumors exhibiting TRAIL-receptors staining on cell membranes in our study. We found that 56% of tumor samples displayed no membrane staining for TRAIL-R1 and 19% for TRAIL-R2 with the extent of membrane staining varying inversely with the cytoplasmatic staining, suggesting that internalization of TRAIL-receptors could represent a mechanism for the loss of functional TRAIL receptors as a distinctive feature of pancreatic cancer cells, a hypothesis recently corroborated by other studies in vitro [11], [31].…”
Section: Discussionsupporting
confidence: 83%
“…The cell surface expression of DR4 or DR5 is a key determinant of tumor sensitivity to the TRAIL-DR targeted therapies. 44 To examine whether KDM4A inhibitor C-4 induced DR5 expression at cell surface, we immunoprecipitated the receptors from the cell surface after cells were treated with C-4. We used an immunoprecipitation method 45 instead of flow cytometry because of the auto-fluorescence activity of C-4.…”
Section: Resultsmentioning
confidence: 99%
“…DR5 mRNA level was not affected; thus, the loss of DR5 protein expression could be attributed to autolysosomal degradation. As shown in monolayer cancer cells [23,37], a deficiency in the cell surface DR5 is correlated with resistance to TRAIL induced apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that breast cancer cellular sensitivity to TNF death ligands is correlated with the corresponding death receptor (DR) expression on the plasma membrane [23,37]. To test this possibility in the non-adherent cultured cells, we performed flow cytometry analysis using antibodies specific to DR4, DR5, Fas, and TNFR1 respectively.…”
Section: Non-adherent Culture Selectively Decreases Dr5 Surface and Tmentioning
confidence: 99%